111 Medisense technology for breast cancer. (3rd November 2019) - Misro, Aswini; Sharma, Vikash
Abstract : Introduction: It is not uncommon for a patient coming to the NHS to present with investigations and treatments done in EU countries and outside the EU for various medical and surgical conditions. Many times, reports are written in languages other than English and therefore does not to contribute to medical consultations. Another issue with the patients is that they feel helpless and frustrated when they can't understand what the reports mean for them. To resolve these problems, we developed a technology called Medisense is a medical report image capture, data extraction, validation and interpretation technology. By using this technology, doctors and patients can take a snap of the picture of any report and get an instant translation, interpretation and review of the report. Study design: In the current study, we carried out 97 cases of breast cancer histopathology reports of various patients. The test was carried out using a specified protocol in a test environment. Results: The study results show that in all the 97 cases, the image capture was successful. However, the data extraction was successful only in 93 cases. In 90 cases, the data interpretation was correct. In the 4 instances where image capture was not successful, the poor printing quality of the report(n=1), folds and creases in the report(n=1), and technical error(n=2) was responsible. Conclusion s: Medisense will be a helpful tool in medical consultations when a patient arrives with a report in a non-native language. This would also help patients interview and interpretation of their medical reports. Further studies and improvements are required to optimise this technology further.